1984
DOI: 10.1128/mcb.4.1.151
|View full text |Cite
|
Sign up to set email alerts
|

An X-linked gene affecting mouse cell DNA synthesis also affects production of unintegrated linear and supercoiled DNA of murine leukemia virus.

Abstract: To identify specific cellular factors which could be required during the synthesis of retroviral DNA, we have studied the replication of murine leukemia virus in mouse cells temperature sensitive for cell DNA synthesis (M. L. Slater and H. L. Ozer, Cell 7:289-295, 1976) and in several of their revertants. This mutation has previously been mapped on the X chromosome. We found that a short incubation of mutant cells at a nonpermissive temperature (39°C) during the early part of the virus cycle (between 0-to 20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…35,[65][66][67][68][69] Tagged ecotropic and amphotropic murine leukemia virus (MLV) and GaLV envelope proteins have been used to demonstrate that retrovirus binding to target cells depends on the receptor density and envelope binding. [65][66][67][68] Analysis of a cell line with an inducible GALVR gene showed that a 4-to 5-fold increase in GALVR mRNA led to a 150-fold increase in the frequency of GALV transduction.…”
Section: Discussionmentioning
confidence: 99%
“…35,[65][66][67][68][69] Tagged ecotropic and amphotropic murine leukemia virus (MLV) and GaLV envelope proteins have been used to demonstrate that retrovirus binding to target cells depends on the receptor density and envelope binding. [65][66][67][68] Analysis of a cell line with an inducible GALVR gene showed that a 4-to 5-fold increase in GALVR mRNA led to a 150-fold increase in the frequency of GALV transduction.…”
Section: Discussionmentioning
confidence: 99%
“…The Temin, 1982;Hsu and Taylor, 1982;Richter et al, 1984;Springett et al, 1989;Miller et al, 1990), although this is not true of all cells and all retroviruses (Lewis et al, 1992). Several studies have indicated that S phase is critical for integration (Harel et al, 1981;Humphries et al, 1981;Hsu and Taylor, 1982;Springett et al, 1989;Miller et al, 1990), although precisely what takes place during this phase is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that cellular DNA replication is required for integration of murine leukemia virus DNA into the host genome of mammalian cells (14,15). However, 97% of purified mouse stem cells are in the Go or G1 phases of the cell cycle (16).…”
mentioning
confidence: 99%